3D Catheter Angiography. Issue 2 (1st April 2003) - Soh, Calvin; Sellar, Robin
Abstract : A 42-year-old woman presented with a classical history of a subarachnoid haemorrhage. An initial CT brain scan showed diffuse subarachnoid blood, equally distributed in Sylvian fissures and in the interhemispheric fissure. Two conventional cerebral angiograms had been performed and showed no aneurysm. In view of her age, clinical presentation and CT findings, a further catheter angiogram was performed, which showed a slight bulkiness at the left middle cerebral artery bifurcation (Fig. 1). However, the 3D angiogram revealed a definite middle cerebral artery aneurysm, measuring only 2 mm in size (Fig. 2). This was successfully treated with endovascular coiling Ruptured intracranial aneurysms have a significant re-bleeding risk of 15–20% in the first 2 weeks. Therefore, early confirmation of an aneurysm facilitates prompt treatment and catheter angiography remains the gold standard technique. But in recent years, three-dimensional rotational angiography has revolutionized catheter angiography. This technique involves selective carotid catheterization, and a